Evaluation of collateral status and outcome in patients with middle cerebral artery stenosis in late time window by CT perfusion imaging - Ban, Mengke; Han, Xue; Bao, Wanli; Zhang, Hongli; Zhang, Ping (Frontiers in Neurology, 2022)
Objectives: Collateral status (CS) is a crucial determinant of outcome in patients with ischemic stroke. We aimed to test whether the cerebral blood volume (CBV) and cerebral blood flow (CBF) based on computed tomography perfusion (CTP) measurements can quantitatively evaluate CS and explore the predictive ability of CTP parameters in determining clinical outcomes in patients with MCA severe stenosis or occlusion presenting beyond 24 hours. Materials and Methods: In this retrospective study, data obtained from September 2018 to March 2022 in consecutive stroke patients caused by isolated middle cerebral artery severe stenosis or occlusion were reviewed within 24-72 hours after onset. Correlation between the collateral score systems assessed with CT angiography (CTA) and CTP parameters was calculated using the Spearman correlation. The optimal threshold of the CBV ratio for predicting a good outcome was determined using receiver operating characteristic curve (ROC) analysis. Results: A total of 69 patients met inclusion criteria. Both the CBV ratio and the CBF ratio had significant correlation with collateral score systems assessed with CTA (CBV ratio and Tan score: rs = 0.702, P < 0.0001; CBV ratio and regional leptomeningeal collateral (rLMC) score: rs = 0.705, P < 0.0001; CBV ratio and Miteff score: rs = 0.625, P < 0.0001. CBF ratio and Tan score: rs= 0.671, P < 0.0001; CBF ratio and rLMC score: rs= 0.715, P < 0.0001; CBF ratio and Miteff score: rs=0.535, P < 0.0001). ROC analysis revealed the CBV ratio performed better than the qualitative collateral assessments and the CBF ratio in the prediction of a favorable 90-day modified Rankin scale score. The CBV ratio was a useful parameter that predicted a good functional outcome (area under the curve [AUC], 0.922; 95%CI, 0.862 ±0.982). Conclusions: In late time window stroke patients, the CBV and CBF ratio on CTP may be valuable parameters for quantitatively revealing the collateral status after stroke. In addition, the CBV ratio was the predictor of clinical outcomes in patients with MCA severe stenosis or occlusion.